A dynamic model of endogenous development: the role of pioneers - Usvitskiy, Alexander (Social choice and welfare, 2024)
We investigate a dynamic development process which involves heterogeneous agents making location choices. In our spatial model agents differ from each other by the impact they have on the development dynamics. In equilibrium, a high impact agent, the pioneer, sacrifices some short-run benefits and chooses an underdeveloped location. The pioneer improves that location and creates incentives for other agents to choose it later in the game. We design a laboratory experiment to test various comparative statics of the model and analyze the role of pioneers as well as the effect that early investments in public goods have on long-run outcomes. Our findings are consistent with theoretical predictions — high impact subjects tend to choose pioneering more frequently than other agents. As predicted, improvements in initial conditions through early investments in public goods significantly affect the dynamics of the system and can lead to substantial welfare improvements. Moreover, learning and experimentation play a significant role in our experiments and help subjects’ behavior to match point predictions of the model. We also observe behavioral deviations such as when some low impact subjects consistently act as lesser pioneers and also choose the underdeveloped location. Such behavior can be treated as growing cooperation and linked to Pareto improvement concerns over the outcomes of previous games.